Ação rescisória por violação aos precedentes : novos rumos sobre a aplicabilidade do enunciado 343 da súmula de jurisprudência do Supremo Tribunal Federal - Manzano, Marina Minassa (2024)
The consolidation of the Code of Civil Procedure through Law 13.105, enacted on March 16, 2015, ushered in a new era in the civil procedural system. Among the various innovations and changes made, the rescissory action now has the possibility of being brought against a decision that manifestly violates a legal rule. At the same time, the CPC/2015 instituted important changes that improved the system of precedents. Based on this new context, many discussions have arisen, with special involvement of the theory of interpretation of the law, the theory of precedents, the legal norm and Supreme Court precedent 343. The purpose of this study is to analyze the applicability of STF Precedent 343 as a control instrument to the “ação rescisória” based on article 966, V of the CPC/2015, based on the current theory of precedents, the theory of interpretation and the historical context of the origin and approval of the precedent